2013
DOI: 10.1111/ina.12073
|View full text |Cite
|
Sign up to set email alerts
|

Radon in indoor air of primary schools: a systematic survey to evaluate factors affecting radon concentration levels and their variability

Abstract: On average, radon concentrations are substantially higher in schools in villages than in schools located in towns (double,on average). Annual radon concentrations exceeding 300 Bq/m3 were found in 5% of primary schools (generally on ground floors of schools in villages). The considerable variability of radon concentration observed between and within floors indicates a need to monitor concentrations in several rooms for each floor. A single radon detector for each room can be used provided that the measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
5
28
1
Order By: Relevance
“…Weighting the Rn concentration for the number of children attending each school and kindergarten gives the weighted mean value of 54.5 Bq m −3 . These results are in a good agreement with the values measured in towns of Southern Serbia . Descriptive statistics of the measured values are presented in Table .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Weighting the Rn concentration for the number of children attending each school and kindergarten gives the weighted mean value of 54.5 Bq m −3 . These results are in a good agreement with the values measured in towns of Southern Serbia . Descriptive statistics of the measured values are presented in Table .…”
Section: Resultssupporting
confidence: 87%
“…In order to assess and control the exposure of young population, systematic surveys of radon levels in schools and kindergartens have been carried out in many countries all over the world . The scope of these investigations conducted in our country has mainly covered the regions of Southern and Northern Serbia .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the latter and as far as the authors’ knowledge goes, in the last five years 19 studies regarding radon in indoor air of nursery and primary schools can be found. The majority of them were only focused on primary schools [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], while others also considered nursery schools [ 10 , 22 , 23 , 24 , 25 , 26 ] and some others only considered nursery schools [ 27 , 28 ]. The extent of the studies varied considerably from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its physical characteristics, presented in classical literature such as Fleischer et al . [], Tanner [], Nazaroff and Nero [], Nazaroff [], and Porstendorfer [], the radioactive noble gas 222 Rn is widely used by the scientific community to study a number of different research topics, such as (i) to improve inverse transport models, which are used to calculate emissions of greenhouse gases (GHGs) [ Biraud et al ., ; Hirao et al ., ; Locatelli et al ., ]; (ii) to study atmospheric transport and mixing processes within the planetary boundary layer [ Zahorowski et al ., ; Galmarini , ; Vinuesa et al ., ; Baskaran , ; Chambers et al ., , ; Williams et al ., , ; Grossi et al ., ; Vogel et al ., ; Hernández‐Ceballos et al ., ; Vargas et al ., ]; (iii) to improve radon flux inventories [ Szegvary et al ., ; Griffiths et al ., ; López‐Coto et al ., ; Karstens et al ., ]; (iv) to experimentally estimate GHGs fluxes by using the Radon Tracer Method [ Levin et al ., ; Vogel et al ., ; Wada et al ., ; Grossi et al ., ]; (v) to understand the influence of climate change on the atmospheric radon increase and its associated health risks [ Nazaroff , ; Bochicchio et al ., ; Bossew et al ., ]; and (vi) to refine baseline selection and characterization techniques and analyze air mass history and fetch at remote sites [ Zahorowski et al ., ; Chambers et al ., , , ].…”
Section: Introductionmentioning
confidence: 99%